STAMP2 increases oxidative stress and is critical for prostate cancer. Issue 3 (13th February 2015) - Jin, Yang; Wang, Ling; Qu, Su; Sheng, Xia; Kristian, Alexandr; Mælandsmo, Gunhild M; Pällmann, Nora; Yuca, Erkan; Tekedereli, Ibrahim; Gorgulu, Kivanc; Alpay, Neslihan; Sood, Anil; et al.
Abstract The six transmembrane protein of prostate 2 (STAMP2) is an androgen‐regulated gene whose mRNA expression is increased in prostate cancer (PCa). Here, we show that STAMP2 protein expression is increased in human PCa compared with benign prostate that is also correlated with tumor grade and treatment response. We also show that STAMP2 significantly increased reactive oxygen species (ROS) in PCa cells through its iron reductase activity which also depleted NADPH levels. Knockdown of STAMP2 expression in PCa cells inhibited proliferation, colony formation, and anchorage‐independent growth, and significantly increased apoptosis. Furthermore, STAMP2 effects were, at least in part, mediated by activating transcription factor 4 (ATF4), whose expression is regulated by ROS. Consistent with in vitro findings, silencing STAMP2 significantly inhibited PCa xenograft growth in mice. Finally, therapeutic silencing of STAMP2 by systemically administered nanoliposomal siRNA profoundly inhibited tumor growth in two established preclinical PCa models in mice. These data suggest that STAMP2 is required for PCa progression and thus may serve as a novel therapeutic target.